Penerapan Extreme Programming Untuk Mengakomodir Perubahan Kebutuhan Pengguna Dalam Pembuatan Aplikasi Persediaan - Ria Ulandari; Nurfia Oktaviani Syamsiah; Reza Maulana (LPPM Universitas Bina Sarana Informatika, 2021)
Inventory is very important for a company, including trading companies. Good inventory management is one of the things to maintain company liquidity. Utilization of inventory information systems is a change that should be done so that company goals are achieved in a shorter time and with minimal costs. Making an information system for a company whose business has been running stably requires a special method so that the system that will be used can be immediately utilized in accordance with running business processes. For this reason, the involvement of system users from the beginning to the end of the system creation stage is very necessary, and the flexibility of changing needs must also be accommodated properly by system developers. Extreme Programing (XP) answers these expectations, because of its flexibility that is able to deliver a system according to user needs, which often change in the span of system development. The Inventory Application at the Al Akram Division is a case study that was raised in this research. By utilizing XP, the researcher succeeded in making the Inventory application (AkaDia) with the achievement of user acceptance test results reaching 94%.